Peningkatan Literasi Pembayaran Non-Tunai di Pasar Badung Melalui Edukasi dan Sosialisasi QRIS - Surya Dharma Kumara, Anak Agung Bagus; Kalfika Anggria Wardani, Kadek Devi (Politeknik Negeri Jember, 2023)
Pasar Badung as a traditional trading center has great potential to adopt a non-cash payment system to increase transaction efficiency and convenience. Pasar Badung is also known as the economic heart of Bali Province. This service activity aims to increase consumer literacy and understanding of digital payments in the form of QRIS. This activity was assisted by an informative poster entitled